Influence of 10-Methacryloyloxydecyl Dihydrogen Phosphate on Cellular Senescence in Osteoblast-Like Cells - Ju Yeon Ban; Sang-Im Lee (The Korean Society of Dental Hygiene Science, 2023)
Background: Resin-based dental materials release residual monomers or other substances from incomplete polymerization into the oral cavity, thereby causing adverse biological effects on oral tissue. 10-Methacryloyloxydecyl dihydrogen phosphate (10-MDP), an acidic monomer containing dihydrogen phosphate and methacrylate groups, is the most commonly used component of resin-based dental materials, such as restorative composite resins, dentin adhesives, and resin cements. Although previous studies have reported the cytotoxicity and biocompatibility in various cultured cells, the effects of resin monomers on cellular aging have not been reported to date. Therefore, this study aimed to investigate the effects of the resin monomer 10-MDP on cellular senescence and inflamm-aging in vitro.Methods: After stimulation with 10-MDP, MC3T3-E1 osteoblast-like cells were examined for cell viability by WST-8 assay and reactive oxygen species (ROS) production by flow cytometry. The protein and mRNA levels of molecular markers of aging were determined by western blotting and RT-PCR analysis, respectively. Results: Treatment with 0.05 to 1 mM 10-MDP for 24 hours reduced the survival of MC3T3-E1 cells in a concentration-dependent manner. The intracellular ROS levels in the 10-MDP-treated experimental group were significantly higher than those in the control group. 10-MDP at a concentration of 0.1 mM increased p53, p16, and p21 protein levels. Additionally, an aging pattern was observed with blue staining due to intracellular senescence-associated beta-galactosidase activity. Treatment with 10-MDP increased the levels of tumor necrosis factor-α, interleukin (IL)-1β, IL-6 and IL-8, however their expression was decreased by mitogen-activated-protein-kinase (MAPK) inhibitors. Conclusion: Taken together, these results suggest that the exposure of osteoblast-like cells to the dental resin monomer 10-MDP, increases the level of cellular senescence and the inflammatory response is mediated by the MAPK pathway.